Analisis Hukum terhadap Penerapan Prinsip Transparansi dalam Pemasaran Produk Asuransi: (Studi Kasus pada PT. Generali Medan) - Tengku Damara Alya; Annisa Sativa (CV Rewang Rencang, 2025)
The lack of transparency in insurance product marketing often leads to consumer dissatisfaction and an increase in legal disputes. According to data from the Financial Services Authority (OJK) in 2022, there were 1,291 complaints related to insurance products, with most grievances arising from discrepancies in marketing information. This study aims to analyze the implementation of transparency principles in insurance product marketing at PT Generali Medan, identify challenges faced, and evaluate the company's responsibility in cases of misinformation provided to customers. Using an empirical juridical method, the study found that although PT Generali Medan has implemented transparency through clear information delivery, disclosure of risks and benefits, and compliance with Financial Services Authority Regulation No. 8 of 2024, several challenges remain, including the complexity of insurance information, limited understanding among prospective customers, and inconsistencies between information provided by agents and policy provisions. To address these issues, the company has adopted strategies such as simplifying product communication, digitalizing information, providing agent training, and strengthening consumer protection mechanisms. This study recommends strengthening OJK regulations on insurance product marketing, enhancing financial literacy among potential customers, and optimizing digital technology to ensure insurance product information is more accessible and comprehensible. With improved transparency, it is expected that disputes will decrease, and public trust in the insurance industry will increase.